The Role of Social Capital in Village Owned Business Entities (BUMDes) on Village Development (Case Study in Pujonkidul Village, Pujon District, Malang Regency) - Rona Rio AKBAR; Maryunani MARYUNANI; Sasongko SASONGKO (Indonesia Strategic Sustainability, 2023)
This study aims to determine what social capital affects the management of BUMDes for village development and to find the elements of social capital to help solve existing problems. By using qualitative research methods, this study seeks to explore the elements and roles of existing social capital and then analyze how this social capital plays a role in solving the problems faced. The results of research and observations of all elements of social capital, namely trust, network, norm, and reciprocal, are all contained in the management of BUMDes. However, the most dominant is the network of all existing elements, thanks to the breadth of relationships and networks. This study also proves that the solution to the problems that exist in the parking business unit, namely the problem of irregular parking by visitors due to the available parking is no longer able to accommodate the vehicles of visitors to the rice field cafe on certain days, so reciprocal is the solution to this problem. Mutual benefit between residents and parking unit managers. Then from the side of trust, the existence of mutual trust between the villagers and the manager of the rice field cafe will strengthen the kinship so that no more problems arise.